Debt Policy, Reputable External Auditor, Company Size, And Profit Quality - Barnabas Tridig S.; Bram Hadianto; Indra Purnama Setiawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The financial report describes company performance before the users: public investors and creditors. Moreover, this report must deliver superior profits to display the beneficial information. For this reason, this study attempts to know its determinants by utilizing causing factors, like debt policy and reputable external auditors as the primary variable and company size as the control. Besides, this study sets the companies in the retail trade industry in the Indonesian capital market from 2013 until 2018 as the population, where a simple random sampling technique is utilized to grab the samples. After that, this study employs the regression model and related statistical features to check the intended hypotheses. After examining them statistically, this study reveals that debt policy and the company size affect profit quality positively. However, reputable external auditors do not influence this quality.